When They Feel Heard: Exploring Comfort Care by Pediatric Hematology-Oncology Nurses. - Pilla, Mary Cate; Bowers, Teresa; Chappell, Kate K. (Oncology Nursing Forum, 2026)
PURPOSE: To explore how nurses comfort pediatric hematology-oncology (PHO) patients, examine nurses' confidence and educational preparation in providing comfort, and inform recommendations for enhancing new nurses' readiness. PARTICIPANTS & SETTING: Seventeen PHO nurses in the southeastern United States were recruited through professional networks and PHO-focused organizations to complete an anonymous online survey. METHODOLOGIC APPROACH: PHO nurses completed a survey with 12 closed and 4 openended questions. Open-coding content analysis was used to derive themes about how nurses comfort PHO patients. Demographic data were analyzed using descriptive statistics. FINDINGS: A conceptual model described how nurses comfort PHO patients through dynamic individualized care using the approaches of preparation, comforting presence, listening, and distraction. More experienced nurses appeared to be more likely to identify listening as a comforting approach. Nurses who were more confident using comfort approaches appeared to be more likely to use them. IMPLICATIONS FOR NURSING: Comfort care is a particular priority when caring for a PHO patient. Understanding nurses' readiness to provide comfort and how they approach this key aspect of PHO care strengthens patient care and nursing practice transitions. There are opportunities to increase education and readiness for this nursing role.